Cyanamide-Based Cyclization Reactions for Nitrogen-Containing Heterocycles Synthesis - Wu, Yu-Xin; Liu, Cheng-Liang; Yan, Qian; Chen, Si-Han; Kuang, Zi-Rui; Liu, Han-Wen; Li, Jiang-Sheng; Li, Zhi-Wei (Current Organic Synthesis, 2025)
Nitrogen-containing heterocycles, such as indoles and quinolines, serve as the key scaffolds in numerous pharmaceuticals, pesticides, and natural products. The synthetic methods of nitrogen-containing heterocycles show significant scientific and industrial values. As a chemical intermediate featuring dual functional groups, cyanamide plays a crucial role in organic synthesis, directly affecting the development of new drugs and the design of new materials. Particularly in the synthesis of nitrogen-containing heterocyclic compounds, the cyano group can introduce various groups through radical pathways to synthesize polycyclic N-heterocyclic frameworks, as well as yielding a variety of nitrogen-containing heterocycles through non-radical pathways. This diverse reaction pathway makes the application of cyanamide in chemical synthesis more extensive and flexible. The progress involving cyanamide in the synthesis of quinazoline and quinazolinone, γ-lactams, and other nitrogen-containing heterocyclic frameworks is summarized. The main mechanisms and reaction strategies are emphasized and explicated from the perspective of radical and non-radical synthetic pathways, revealing the potential application value of these compounds in different fields. This review paves the way for the synthesis of various nitrogen-containing heterocyclic compounds, particularly in achieving green chemistry and sustainable development goals. These new methods and ideas are expected to promote the development of more efficient and economical synthesis strategies in the future, thereby advancing the widespread application of nitrogen-containing heterocyclic compounds in pharmaceuticals, agricultural chemicals, and new materials.
Keywords: γ-lactams